Workplace stress: the employer's liability - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Kasi, Arun (LexisNexis Malaysia Sdn Bhd, 2019)
Excessive workload or work demands, stressful deadlines, long working hours, insufficient number of staff, lack of support from co-workers and supervisors, annoying co-workers, dissatisfied customers, hazardous working conditions, job uncertainty and hostile work environment are, among others, some of the commonly known stressors that contribute to occupational or workplace stress. Workplace stress often results in high dissatisfaction among employees in terms of job mobility, burnout, less effective interpersonal relations at work and unsatisfactory work performance. This may be due to several reasons such as persistent lateness or tardiness, taking excessive sick leave and repeated absences. Long-term stress or traumatic events at work can affect the physical as well as physiological health of the worker. An employer has a duty to ensure that the environment at the workplace is safe and conducive, free from threats, intimidation and violence. Considering the above, this article discusses the employer's liability for employee's psychological disturbance arising from occupational or workplace stress and harassment. The discussion will focus primarily on occupational stress arising from bullying, harassment and reprehensible or highhanded manner of a dismissal with particular reference to the law and practice in Malaysia.